Nietzsche e a vida : dos valores metafísicos dogmáticos a uma metafísica de artista - Faria, Gabriel Pereira (2015)
This paper aims to show the metaphysical conception in their impacts on the world and life, as well as the Nietzschean critique to this philosophical tradition, and more, your hypothesis about the world, life and aesthetics as vital phenomenon . Opposing metaphysical in its three aspects religious, moral and philosophical, Nietzsche, thinks the world composed of plural forces together to engage in combat with other sets of forces. Criticizing the world hierarchical, static whose 'being' or essence intended, the author thinks of a movement and aggregation that constitute it. The will to power is something that is within the own strength, so is present at all. Life is will to power, it is endowed with power from the organic level. There is no static hierarchy of 'being', intended essence, life and the phenomenal events is an eternal becoming. The world and life is the will to power, life is a particular case of the will to power, because it operates in the world. Explain the art itself, with Apollonian and Dionysiac natural impulses within us, in fisoológicos states of dream and intoxication. Life is explained through the actions in each action of man, every occurrence is holy, as something to be lived now and forever, no matter what happens. Individualization is an action of creation, and there is the concept of good, evil or obligation, there is only existence. That's all. The esthetic explanation keeps in the community as something eternal generations of sequences.